Compatibility studies of poly(ether imide) with liquid crystal mixtures - Cakar, F.; Ocak, H.; Bilgin-Eran, B.; Cankurtaran, O.; Karaman, F. (NATL INST OPTOELECTRONICS, 2013)
The miscibility of poly(ether imide) (Ultem) and liquid crystal 41[(2S)-2-methylbutoxy]-N-[[4-[(5,5,6,6,7,7,8,8,9,9,10,10,10-tridecafluorodecyl)oxy]phenyl] methylene] benzenamine (MTOPMB) were investigated at 30 C in dilute chloroform solutions by viscometric analysis. The intrinsic viscosity and interaction parameters were determined for individual components and binary Ultem/MTOPMB mixtures in compositions such as 80/20, 60/40, 40/60 and 20/80 (w/w) in chloroform solutions. The miscibility criteria on the basis of the sign of Delta b(m), Delta b(m)', Delta b(m)'' and Delta[eta](m) which are the difference between their experimental and ideal values were used in viscometric analysis. The data suggested that the studied binary mixtures were immiscible except the one of Ultem/MTOPMB: 80/20 (w/w). The miscibility of the mixtures was also studied by differential scanning calorimetry (DSC) and polarised light optical microscopy (POM).
Keywords: Poly(ether imide); Liquid crystal; Miscibility; Viscometry; DILUTE-SOLUTIONS; BLENDS; POLYMER; COPOLYESTER; Materials Science; Optics